The extent of adopting the dimensions of the Blue Ocean Strategy and its impact in the market share: بحث استطلاعي في شركة الحمراء للتأمين (Journal of Accounting and Financial Studies ( JAFS ), 2021)
With the increase in competition between insurance companies in addition to the increasing numbers in the number of insurance companies, whose number decreased to (32) private companies until the end of the year (2020). The blue ocean at the level and its effects on increasing the market share. Therefore, the two researchers tested the hypothesis and the research concluded that there is a relationship A .Also the researcher put some recommendations the most prominent is that the invention is considered one of the successful strategies an d the company has to encourage the employees according to inventive thoughts